(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Ahmadi A, Kavosi MR, Soltanloo H. 2014. Zelkova carpinifolia reservoir from Hyrcanian Forests, Northern Iran, a new sacrifice of Ophiostoma novo-ulmi. Biodiversitas 15: 48-52. Zelkova carpinifolia belongs to the Ulmaceae. It is the only species from Zelkova genus that has been distributed and is native to Iranian forests. This tree species is one of the valuable species that is comprised of endangered plants. Nevertheless, the most of reservoirs of this species have been faced to problems that fungal disease is one of the important and lethal disturbance. This study was conducted to identify the main disturbance which has been resulted in Z. carpinifolia decadence in Daland forest reservoir, North of Iran. The study has ensured that O. novo-ulmi is the fungal pathogen in this forest reservoir. It can be reminded that this pathogen had been previously found in Ulmus genus which has been created devastating event in these noteworthy reservoirs. Some symptoms which were observed in field comprising flagging and wilting of leaves. Bark beetle galleries and occlusion of xylem vessels were the other evidence of fungal disease. In light of laboratory results, the fungi colony was fluffy, light-colored and fast-growing. The different shapes of fungi growth like white fibrous and flower shape or dark petaloid shape were observed. Mean colony diameters of O. novo-ulmi were 3.72 ±0.16 mm/day in the dark at 20 °C. Simultaneously, Microscopic analysis of sexual and asexual systems of O. novo-ulmi using a light microscope, a stereo microscope, and a scanning electron microscope revealed that it had morphological features of sporothix, pesotum, yeast-like and perithecium synanon morphology.